MANAGEMENT OF LEGUME AS LAND COVER CROP AND EMPTY BUNCH FOR THE NITROGEN EFFICIENCY IN INCEPTISOLS AT OIL-PALM PLANTATION - Supriyadi Supriyadi; Robertus Sudaryanto; Purwanto Hadisudarmo; Andries Safrudin (Sains Tanah - Jurnal Ilmu Tanah dan Agroklimatologi, 2016)
The research aimed to know the kind of legume cover crop which more suitable to be cultivated especially in area of Natar, South Lampung and to know the efficiency of N supply. It used a single Completely Randomized Block Design (CRBD) consisted of 4 treatments (several kinds of debris), covering: kacang benguk (Mucuna cochinchinensis), kacang ruji (Pueraria javanica), and oil-palm empty bunch compared to one which no debris added (control). Data analyzed by regression, F test (α 5%; or Kruskal-Wallis), DMR test (α 5%; or Mood Median) and correlation test. Result showed that Pueraria javanica (kacang ruji) was more suitable to be cultivated. Regression showed that management of empty bunch tend to enhance the ratio of NH4+/N-mineral as indicator of N supply efficiency, while the management of Pueraria javanica tend to decrease the ratio of NH4+/N-mineral. The degradation of soil NO3- concentration in the treatment of empty bunch was followed by the degradation of soil nitrification potential and the enhancement of heterotrofic bacteria. The enhancement of soil nitrification potential in the Pueraria javanica and Mucuna cochinchinensis management was followed by the degradation of soil pH.